Metamorfozy Platońskiej „metafory słońca” (Respublica 509b) w hetero- i ortodoksyjnej teologii (I-III w.): gnostycyzm, Klemens z Aleksandrii i Orygenes - Mrugalski, Damian (Vox Patrum, 2018)
The metaphor of the sun, in which Plato (Republic 509b) compares the idea of the Good to the sun that dwells above the earth yet affects the phenomena occurring on it, was an inspiration for both heretical and orthodox theology in the first Christian centuries. The Gnostics, Clement of Alexandria and Origen all believed that God, like the Platonic idea of the Good, is radically transcendent in relation to the world, but at the same time is the cause of everything that exists in it. Unlike Plato, who believed that the idea of the Good is knowable and can be the subject of science, the Christian theologians of the first centuries believed that God was like a blinding light. This means that God, according to them, though intelligible, is unknowable in His essence. Therefore, God cannot be the subject of science. Another modification of the Platonic metaphor was the introduction of the element of sunlight, to which the philosopher from Athens did not refer. For the Gnostics, the rays of the sun were “eons” – spiritual beings that existed in the space between the first principle of all things and the material world. For Clement and Origen, the light that comes from the sun was the Son – the power and wisdom of God. In contrast to the Gnostics, who believed in the progressive degradation of the spiritual world through successive emanations, the Alexandrian Fathers believed that the Son possessed all the knowledge of God and therefore revealed to man the true God. Yet the revelation of God by the Son, and even the grace that assists human beings in the process of learning about God, do not give man complete knowledge of the essence of God. Thus the Gnostics, Clement and Origen, despite some doctrinal differences, all accepted the concept of the radical transcendence of God on the ontological and epistemological levels.